The Chinese higher education system and the impact of gender - Jinsong, Gu; Hua, Jiang (My University, 2010)
The focus of the dissertation lies on the situation of males and females in Chinese universities, including the allocation between males and females in different positions and disciplines, as well as an analysis of reasons for these differences and the meaning of women’s involvement in universities. The dissertation consists of two parts. The first part is based on theories and previous research by different researchers; the second part is an empirical study from the authors. There are 4 chapters in the theoretical part. The first chapter offers an overview of the Chinese education system; the second chapter describes the students’ situation in Chinese higher education; the third chapter focuses on recent developments in teacher training; the last chapter is dealing with the female teachers in Chinese higher education. The second part, chapter 5, presents the results of an empirical study concerning biographies, motivations and orientations of Chinese male and female university teachers. The final chapter, chapter 6, presents a summary of the main research results. In addition, this chapter opens up for an international comparison between Chinese and German universities.
The structure of Chinese education system and previous research and an empirical study
Keywords: Schule; Hierarchie; Universität; Arbeitsmarkt; Geschlecht; Frauen; Männer; Bildung; 370 Bildung und Erziehung; China